1995
DOI: 10.1111/j.1365-246x.1995.tb07002.x
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on mantle viscosity based upon the inversion of post-glacial uplift data from the Hudson Bay region

Abstract: S U M M A R YWe outline two parametrizations for post-glacial relative sea-level (RSL) histories associated with previously glaciated regions. The first parametrization is based on a site-dependent normalization of the RSL history, while the second involves the estimate of a site-dependent (logarithm of the) inverse decay time for the exponential-like form which characterizes these histories. Both parametrizations are shown to yield data sets which are relatively insensitive to the details of the late Pleistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 30 publications
10
96
0
Order By: Relevance
“…proposed by Peltier (1998;1999) for region SE are markedly smaller than previous estimates for region RG (Peltier, 1994;Mitrovica and Peltier, 1995;Peltier, 1996). Similar to Mitrovica et al (2000), they and Hager used the RSL data without correction, but limited the time window to 6.8 ka, resulting in a relaxation time of (6.3 ± 1.0) ka for region RG.…”
Section: Fang and Hager (2002) Also Noted That The Relaxation-time Esmentioning
confidence: 95%
“…proposed by Peltier (1998;1999) for region SE are markedly smaller than previous estimates for region RG (Peltier, 1994;Mitrovica and Peltier, 1995;Peltier, 1996). Similar to Mitrovica et al (2000), they and Hager used the RSL data without correction, but limited the time window to 6.8 ka, resulting in a relaxation time of (6.3 ± 1.0) ka for region RG.…”
Section: Fang and Hager (2002) Also Noted That The Relaxation-time Esmentioning
confidence: 95%
“…There are a number of problems associated with this procedure, particularly in regard to our present effort at establishing decay times. First, large temporal gaps exist in the geological data, and this requires extensive (and subjective) interpolation [see Mitrovica and Peltier, 1995]. Second, the decay times associated with the RSL trends may not be an accurate representation of the true observational constraints.…”
Section: Glacial Isostatic Adjustment' Theory and Observablesmentioning
confidence: 99%
“…For example, the primary constraint on mantle viscosity remains observations of Fennoscandian and Laurentide postglacial rebound [Haskell, 1935;Nakada and Lambeck, 1989;Mitrovica and Peltier, 1995], and although some controversy remains concerning the gross radial viscosity structure of the mantle [e.g., Nakada and Lambeck, 1989; Tushingham and Peltier, 1992], all lines of evidence seem to point toward a highly viscous lower mantle [Mitrovica and Forte, 1997]. In fact, Mitrovica [1996] has shown that the disagreements within the community may be traced to a misinterpretation of the Haskell [1935] constraint and that rebound data are indeed consistent with a highly viscous lower mantle.…”
Section: Introductionmentioning
confidence: 99%